The Development of Project-Based Dakon-Assisted Teaching Modules to Improve Students' Cognitive Abilities and Collaboration Skills - Razifa Syifqi Zulayfiyah; Mohammad Syaifuddin; Siti Inganah; Fahad Abdul Ghani (Journal of Teaching and Learning Mathematics, 2026)
Initial observations indicate that the cognitive ability of mathematics in the material of number patterns is relatively low and students' collaboration skills have not been seen. So the purpose of this study is to produce a valid, practical, and effective project-based dakon-assisted teaching module; in order to determine students' cognitive abilities and collaboration skills. In its learning, this study raises the culture of traditional Javanese games, namely Dakon. The method used in this study is the Research and Development (R&D) method with the ADDIE model. Data were obtained using pre-test-post-test instruments, LKPD, collaboration skills assessment questionnaires, and practicality questionnaires for teaching modules. The results of the study showed that: (1) The validity results of the teaching module reached 3.68 (very valid); pre-test-post-test validation of 3.73 (very valid); LKPD validation of 3.55 (valid); questionnaire validation of 3.70 (very valid) so that the teaching module and its instruments are said to be suitable for use in learning; (2) The results of the practicality questionnaire for the teaching module reached 87% score, so the application of the teaching module is said to be very practical. In addition, the teaching module has been tested on small groups and large groups of 24 students; (3) the N-Gain results obtained were 82%, which means that the application of the teaching module in the implementation of large group tests is said to be effective in improving students' cognitive abilities; (4) Furthermore, the results of collaboration skills obtained from the questionnaire data obtained a figure of 3.70 (very effective) which means that the teaching module is said to be very effective in improving students' collaboration skills.